TANGGUNG JAWAB PERUSAHAAN PENERBANGAN TERHADAP KERUGIAN BARANG BAGASI TERCATAT PENUMPANG PADA PENERBANGAN DOMESTIK (STUDI PADA PT.GARUDA INDONESIA AIRLINES MEDAN) - Harry Fauzi; Hasim Purba; Jelly Leviza; Yefrizawati Yefrizawati (USU LAW JOURNAL, 2016)
ABSTRACT   Air transport is an activity is the transportation of passengers and goods in one or more travel from one airport to another airport, which is one of the important means of air transport then has to be laid out in such a way so that it is able to manifest the protection security, the safety of passengers, baggage and goods are recorded, which has responsibility for passenger and baggage items listed, as listed in Articel 144 and 146 Chapter Law Number 1 Year 2009 on a Flight that is the basis of the carrier against the baggage items listed passengers who suffered losses during the flight, having regard to the magnitude of the damages given to transport to passengerd listed in the regulation of the minister of transportation Number 77 in 2011 About The Responsibility of air freight Carrier. Therefore, this thesis seeks to analyze the legal protection of baggage items listed passengers, the loss of the carrier’s responsibility and how a dispute over luggage goods recorded a loss of passengers.   Key Words: Responsibility, The Airlines, The Baggage Is Recorded